Frequência auto-controlada de conhecimento de resultados e traço de personalidade na aprendizagem de uma habilidade motora seqüencial - Kaefer, Angelica (2009)
The relationship between extroversion-introversion personality trait and the selfcontrolled frequency of extrinsic feedback, in the learning of a sequential timing motor skill in adults was investigated in the current study. The subjects answered to the Eysenck Personality Questionnaire (EPQ) for the personality evaluation of. 56 citizens. University students of both genders had been selected through the EPQ and had then been submitted to a motor task that consisted of pressing computer keyboard keys, with specific space and timing sequence established by the experimenter. The experiment counted on phases of acquisition, retention and transfer. The retention and transfer phases were carried out 24 hours after the acquisition phase. The subjects were distributed in 4 groups, formed by the combination of the trace (extroversão/introversion) and frequency of KR (selfcontrolled and externally controlled). The dependent variable used in the study was the partial errors in absolute and relative timing in each block. The results indicated superior learning for the groups that had practiced in a self controlled schedule. Complementary analyses were carried out, evidencing inferior learning for the group of introverts that requested more KR at the beginning of the practice and less at the end, in relation to all the other groups. Hence, these complementary analyses demonstrated a significant interaction between personality trait and KR frequency in relation to a high or low request of KR in relative timing, that is; introverts who requested high frequency of KR learned more than introverts who requested low frequency of KR and extroverts who requested low KR frequency learned more than extroverts who requested high KR.